Women and Sexual Contracts in Divakaruni's Arranged Marriage - Andini Rahma Irwanti; Miftahur Roifah (Universitas Airlangga, 2022)
This study examines the position of women in Divakaruni's collection of short stories. This study aims to look at what the position of women is depicted in Divakaruni’s collection of short stories Arranged Marriage, and uses the narrative of the sexual contracts. This theory was chosen because it can investigate the complications revealed. Therefore this theory is well-suited to determining the position of women in Divakaruni's collection of Arranged Marriage stories. The data is presented in the form of character utterance and author narration. This study used a qualitative descriptive method to analyze the data. A woman is a property where the property owner is free to do whatever he wants. The property owner has the right to be angry and to speak harshly when he is upset. Women must obey whatever men say if they do not want to be physically abused.